TRANSLATION METHODS AND DEGREE OF EQUIVALENCE IN ENGLISH-INDONESIAN TRANSLATION OF LEO TOLSTOYâ€™S â€œGOD SEES THE TRUTH BUT WAITSâ€ (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2018)
This research is conducted to identify the methods used by the translator in translating Tolstoyâ€™s God Sees the Truth, But Waits, to describe the degree of equivalence between the English original version and the Indonesian translation of the short story, and to show the relation between them. The translation method used in this research are proposed by Newmark, while the degrees of equivalence are analyzed using Bellâ€™s. This research applies qualitative method to describe the aims of this study. The data are analyzed by comparing the English short story and its Indonesian translation. After the data are identified, they are examined to find the relation between the methods used and the degrees of equivalence.The findings of this study show that (1) six translation methods were used to translate God Sees the Truth, but Waits into Indonesian, These include semantic translation, communicative translation, literal translation, adaptation, free translation and word-for-word translation, (2) In terms of the degree of equivalence, it was found that 57 data are partly equivalent with increased meaning, 41 data are fully equivalent, 39 data are non-equivalent with different meaning, 32 data are partly equivalent with decreased meanig and 1 datum are non-equivalent with no meaning, (3) most of the translation methods used produce partly equivalent translation with increased meaning.